Estimation of the time-dependent crustal movements of the Izmit Earthquake - Dogan, U; Ergintav, S; Demirel, H; Çakmak, R; Özener, H (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
The 17 August 1999 Izmit earthquake significantly deformed the earth's crust in the Marmara Region, especially in the Golcuk-Sapanca Zone, Turkey. It broke a 150-km long segment of the northern branch of North Anatolian Fault Zone. The geodetically determined moment magnitude was M-W=7.5. Global Positioning System (GPS) sites, which are a small subset of the Marmara Continuous GPS Network (MAGNET), and survey sites in the region were studied to estimate coseismic and postseismic deformations. using different methodologies with linear, quadratic and exponential kinematic models. Six GPS epochs for these sites, which were carried out before and after the 17 August 1999 Izmit earthquake, were used to define the kinematic models. The quadratic deformation model was also applied to determine the time-dependent crustal movement parameters (velocity and acceleration) of the sites, using the Kalman filter technique. In order to show the differences between the models, the estimated deformation fields on the last epoch were compared. In all models, as expected, the faults near the sites show large coseismic displacements with fault parallel direction, whereas the far sites show small coseismic displacements due to the effects of the Izmit earthquake. Each kinematic model, fitted to the epochs after the earthquake, shows different behaviour. While the linear model shows insufficient results, the nonlinear models (quadratic and exponential) give the best fitted to the postseismic deformations. As a result of Kalman filter analysis, the fault near-sites shows significant velocities with fault parallel direction, whereas the far sites have insignificant velocities. All stations have insignificant accelerations in the last epoch. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: POSTSEISMIC DEFORMATION; Geochemistry & Geophysics